(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article is on the topic of Hermeneutics of Sufi Poetry and studies the methods of poetic interpretation (hermeneutics) of Sufism. Sufism is primarily a philosophical and religious path aimed at understanding the human psyche and its relationship with divine truth. Poetry is an important means of expressing divine and spiritual experiences in Sufism. This article analyzes the gnostic (knowledge) foundations of Sufi poetry, symbolic and mystical layers of meaning, as well as the methodologies and approaches used in their interpretation. The article shows that through the specific forms of expression of Sufi poetry and its hermeneutics, it is possible to understand the relationship between the external and internal worlds of a person more deeply.